Os efeitos da abertura financeira nos anos 90: uma comparação entre países emergentes - Hamberger, Paula Andréa do Valle (2005)
The present dissertation aims to analyse under the hypothesis of externai vulnerability the effects of financial liberalizàtion in the emerging markets of Latin America, Brazil, Argentina, México and Chile, as well as in the Asian countries of Korea and Malasya during de 1990s, after engaging in the neoliberal strategy of economic development. In particular, this work develops a series of indexes of externai vulnerability according to the externai fragility and vulnerability hypothesis in a sample of 1994 to 2003 period, for the qualitative analysis and the period of 1997 to 2003 for empirical data, intending to show us the link between volatile capital flows and the externai structural inviability, causing the externai debt of these emerging markets to increase in tandem with dependence on foreign funds, short or long term, with adverse effects on these economies driving them to financial crises exacerbated by contagious channels. Moreover, the present work entails to examine the levei of similarity between the vulnerability indexes of Latin America and Asia, in terms of the vulnerability of their economies expressed by the indexes examined, as well as the contagious degrees demonstrated by these economies during the financial crises of 1990s and of the beginning of the twenty first century.